Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14153668
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1 Is a Transcription Factor Important for Uveal Melanocyte Development and Associated with High-Risk Uveal Melanoma

Abstract: Uveal melanoma (UM) is a deadly ocular malignancy, originating from uveal melanocytes. Although much is known regarding prognostication in UM, the exact mechanism of metastasis is mostly unknown. Metastatic tumor cells are known to express a more stem-like RNA profile which is seen often in cell-specific embryonic development to induce tumor progression. Here, we identified novel transcription regulators by reanalyzing publicly available single cell RNA sequencing experiments. We identified five transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…And although this gene is very interesting, we could not obtain sufficient samples to analyze MBD4 as a subgroup. Next to the secondary driver mutations, differential expression of the genes FOXD1 [ 38 ], HES6 [ 39 ], ABHD6 [ 40 ], and PRC1 [ 41 ] is associated with metastasis formation in either BAP1 or SF3B1 -mutated UMs. Unfortunately, we do not have transcriptomic information on most of the selected patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…And although this gene is very interesting, we could not obtain sufficient samples to analyze MBD4 as a subgroup. Next to the secondary driver mutations, differential expression of the genes FOXD1 [ 38 ], HES6 [ 39 ], ABHD6 [ 40 ], and PRC1 [ 41 ] is associated with metastasis formation in either BAP1 or SF3B1 -mutated UMs. Unfortunately, we do not have transcriptomic information on most of the selected patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…also developed a prognostic risk model based on basement membrane protein-related genes ( 30 ), and glycosylation-based gene signature and hypoxia-related gene signature were described as well by integrating single-cell analysis and machine learning ( 31 , 32 ). Re-analyzing publicly available single cell RNA sequencing, researchers found that FOXD1 exclusively expressed in high-risk UM and its expression is associated with a poor prognosis, suggesting FOXD1 as a new biomarker for the diagnosis of UM ( 33 ).…”
Section: Biomarkers and Predictive Modelsmentioning
confidence: 99%
“…Melanoma (melanoma malignum) is a malignant neoplasm most commonly found on the skin, originating from melanocytes, and overexposure to harmful UV radiation is considered to be the main cause of its occurrence [30,31]. This neoplasm shows a rather high potential to cause metastasis.…”
Section: Use Of Betulin and Betulinic Acid In The Treatment Of Skin D...mentioning
confidence: 99%